Good Outcome Scores and Low Conversion Rate to THA 10 Years After Hip Arthroscopy for the Treatment of Femoroacetabular Impingement. Issue 10 (29th October 2021) - Büchler, Lorenz; Grob, Valentin; Anwander, Helen; Lerch, Till D.; Haefeli, Pascal C.
Abstract: Background: Arthroscopic treatment of symptomatic femoroacetabular impingement (FAI) has promising short-term to mid-term results. In addition to treating acute pain or impaired function, the goal of hip-preserving surgery is to achieve a lasting improvement of hip function and to prevent the development of osteoarthritis. Long-term results are necessary to evaluate the effectiveness of surgical treatment and to further improve results by identifying factors associated with conversion to THA. Questions/purposes: (1) How do the Merle d'Aubigné-Postel scores change from before surgery to follow-up of at least 10 years in patients undergoing hip arthroscopy for the treatment of FAI? (2) What is the cumulative 10-year survival rate of hips with the endpoints of conversion to THA or a Merle d'Aubigné-Postel score less than 15? (3) Which factors are associated with conversion to THA? Methods: Between 2003 and 2008, we treated 63 patients (65 hips) for symptomatic FAI with hip arthroscopy at our institution. During that period, the indications for using arthroscopy were correction of anterior cam morphology and anterolateral rim trimming with debridement or reattachment of the labrum. We excluded patients who were younger than 16 years and those who had previous trauma or surgery of the hip. Based on that, 60 patients (62 hips) were eligible. A further 17% (10 of 60) of patients were excluded because the treatment was purely symptomatic without treatment of cam- and/or pincer-type morphology. Of the 50 patients (52 hips) included in the study, 2% (1) of patients were lost before the minimum study follow-up of 10 years, leaving 49 patients (51 hips) for analysis. The median (range) follow-up was 11 years (10 to 17). The median age at surgery was 33 years (16 to 63). Ninety percent (45 of 50) of patients were women. Of the 52 hips, 75% (39 of 52) underwent cam resection (femoral offset correction), 8% (4 of 52) underwent acetabular rim trimming, and 17% (9 of 52) had both procedures. Additionally, in 35% (18 of 52) of hips the labrum was debrided, in 31% (16 of 52) it was resected, and in 10% (5 of 52) of hips the labrum was reattached. The primary clinical outcome measurements were conversion to THA and the Merle d'Aubigné-Postel score. Kaplan-Meier survivorship and Cox regression analyses were performed with endpoints being conversion to THA or Merle d'Aubigné-Postel score less than 15 points. Results: The clinical result at 10 years of follow-up was good. The median improvement of the Merle d'Aubigné-Postel score was 3 points (interquartile range 2 to 4), to a median score at last follow-up of 17 points (range 10 to 18). The cumulative 10-year survival rate was 92% (95% CI 85% to 99%) with the endpoints of conversion to THA or Merle d'Aubigné-Postel score less than 15. Factors associated with conversion to THA were each year of advancing age at the time of surgery (hazard ratio 1.1 [95% CI 1.0 to 1.3]; p = 0.01) and preoperative Tönnis Grade 1 compared with Tönnis Grade 0 (no sign of arthritis; HR 17 [95% CI 1.8 to 166]; p = 0.01). Conclusion: In this series, more than 90% of patients retained their native hips and reported good patient-reported outcome scores at least 10 years after arthroscopic treatment of symptomatic FAI. Younger patients fared better in this series, as did hips without signs of osteoarthritis. Future studies with prospective comparisons of treatment groups are needed to determine how best to treat complex impingement morphologies. Level of Evidence: Level IV, therapeutic study.